AmbieGenVAE at the SBFT 2024 Tool Competition - Cyber-Physical Systems Track - Humeniuk, Dmytro; Khomh, Foutse (2024 IEEE/ACM International Workshop on Search-Based and Fuzz Testing (SBFT), 2024)
Testing and verification of autonomous systems is critically important. In the context of SBFT 2024 Cyber-physical systems (CPS) testing tool competition, we present our tool AmbieGenVAE for generating virtual roads to test an autonomous vehicle lane keeping assist system. AmbieGenVAE leverages optimization in a Variational Autoencoder latent space to produce challenging test scenarios. It has achieved the highest score for one of the test subjects and the second-highest final score among 2 other submitted tools.